Masculinities and School Territory in a Rural Educational Institution in Boyacá, Colombia - Barbosa , José; Solís , Daniel (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This article presents findings from qualitative research that analyzed male students’ construction of masculinities and the capitalization of the school territory in a rural educational institution located at Ricaurte, province in Boyacá, Colombia. The investigative process followed an ethno-sociological method and generated information from participant observation and the development of interviews with members of the educational community. The generated data was incorporated into discussions and understandings on the demarcation and occupation of the school territory by male students. As a result, it is indicated that, in the daily school dynamics, a model of hegemonic masculinity is organized through game and imposes hierarchical practices and controls on male students. The masculine performativity at school is manifested in the demarcation of a territoriality that symbolizes masculine domination. It was concluded that, in the educational institution studied, the educational order and the gender order are intertwined, giving rise to masculinities that are multiple, heterogeneous and in constant test by other male counterparts.